Structural and stratigraphic study of the Keewatin-type and Shebandowan-type rocks west of Thunder Bay, Ontario - Brown, Georgina Heather (1985)
Detailed mapping was carried out in the Shebandowan Lakes area and eastward to the Kaministiquia River to study the structural and stratigraphic relationships between the Keewatin and Timiskaming rocks (herein referred to as Keewatin-type and Shebandowan-type, respectively, to avoid connotations of time-stratigraphic equivalence with type areas) of the region. It is believed that the Shebandowan-type rocks are younger than the Keewatin-type rocks. Although no actual contact between the two has been seen in outcrop in the study area, the trend of their contact is discordant with the trend of cleavage in the Shebandowan-type rocks. This, along with the less recrystallized appearance of the Shebandowan-type rocks, and the presence of clasts of jasper in conglomerates of the Shebandowan-type sequence similar in appearance to the jaspilitic iron formation interbedded with the Keewatin-type mafic volcanics, leads to the conclusion that an unconformity separates the two groups of rocks. Recent geochronological work on some of the rocks in the region, carried out by the Ontario Geological Survey, supports this theory. The macroscopic, microscopic and sub-microscopic structure of both groups of rocks was examined in detail. The minor structures seen in outcrop, the examination of thin sections, scanning electron microscope work, and the determination of the magnetic fabric of the rocks all show that the rocks in the present study area contain a single, penetrative, primary cleavage, which has a consistent trend across the whole area. The regional structural picture which emerges from the data is characterized by close-spaced, isoclinal folding with sub-vertical fold axial traces trending roughly east-west. Local variations exist in the eastern portion of the study area where more widely-spaced and open folding is more common. No evidence of a second, significant period of deformation in the present study area has been found.